Optimalisasi Proses Administrasi Layanan Asuransi Oleh PT Jasa Raharja Kota Batam - Betty Krisdayanti S Sihombing; Timbul Dompak (LPPM Universitas Putera Batam, 2023)
The of this research emphasis is to assist researchers in understanding the problem under study using the indicator Optimization of the Insurance Service Administration Process by Pt Jasa Raharja Batam City optimization of the insurance service administration process by PT Jasa Raharja Batam City. According to Articles 1 to 24 of Law/22 of 2009 a traffic accident is an unexpected and unintentional incident on the highway involving two or more vehicles colliding with each other or vehicles with no other road users, where the risks of accidents include minor injuries, serious injuries, death, and only experiencing property loss experienced by one or even both victims. Qualitative research methodology was applied in this study. To describe facts and information in the field, such as social activities, attitudes, events, and beliefs that have occurred or have not occurred at the research site, qualitative research methods are used. Optimization of Insurance Service Administration Process by PT Jasa Raharja Batam City PT Jasa Raharja Batam City cooperates with the police and district/city regional governments in order to improve services for the general public who own motorized vehicles and utilize other road facilities. 33 of 1964 concerning obligatory fees and donations to be collected and collected and then redistributed to people who have had accidents, as insurance for raharja services. Jasa raharja insurance is the protection and guarantee of the state to its people who have an accident, while the object is humans and this insurance provides guarantees against losses caused by accidents.